The theory of plasma heating and confinement in a multislit electromagnetic trap - Lavrent’ev, O.A. (Вопросы атомной науки и техники, 2003)
In the article the circle of questions connected to plasma heating and confinement in a multislit electromagnetic trap with axisymmetric geometry of a magnetic field is considered: plasma formation and heated by electrons injection, electrons cross transfer in a space of coordinates and in a space of speeds, ions losses through ring magnetic slits and axial holes, recuperation and direct transformation of a - particles kinetic energy in electrical one. The accounts of the basic characteristics thermonuclear reactor “Elemag” are offered. В статті розглядається коло питаннь, пов’язаних з нагрівом та утриманням плазми в багатощілинній електромагнітній пастці з осесиметричною геометрією магнітного поля: створення і нагрів плазми з допомогою електронної інжекції; перенос електронів в просторі координат і просторі швидкостей; втрати іонів через кільцеві магнітні щілини та осьові отвори, рекуперація і безпосереднє перетворення кінетичної енергії a-часток в електричну. Приводяться розрахунки основних характеристик термоядерного реактору «Елемаг». В статье рассматривается круг вопросов, связанных с нагревом и удержанием плазмы в многощелевой электромагнитной ловушке с осесимметричной геометрией магнитного поля: образование и нагрев плазмы при помощи электронной инжекции; перенос электронов в пространстве координат и в пространстве скоростей; потери ионов через кольцевые магнитные щели и осевые отверстия; рекуперация и непосредственное преобразование кинетической энергии a-частиц в электрическую. Приводятся расчеты основных характеристик термоядерного реактора «Элемаг».